Effects of nanoparticles zinc oxide and nano cobalt on the germination of soybean (Glycine max (L.) Merr) - Hoe, Pham Thi; Linh, Tran My; Van, Nguyen Tuong; Buu, Ngo Quoc; Mai, Nguyen Chi; Lien, Le Quynh; Ban, Ninh Khac; Thu Hien, Le Thi; Chau, Nguyen Hoai (Vietnam Journal of Biotechnology, 2018)
Nowaday, nanotechnology and nanomaterials have been applied widely as stimulars and micronutrions in agricultural production to increase productivity and quality of important crops. In order to promote the efficiency and stable use of nano metal products for such purpose in Vietnam, several studies have focused on evaluating new metal nanoparticles in different plant species. In this study, the effects of zinc oxide (ZnO) and cobalt (Co) nanoparticles on germination of soybean (Glycine max (L.) Merr), an important crop in Vietnam, were assessed through germination rate, root growth and the expression of important genes. The results showed that DT26 soybean seeds treated with metal nanoparticles at extremely low concentrations accelerated the germination rate and enhanced root growth, however did not affect morphogenesis. Nanoparticles of ZnO of 50 mg/L and Co of 0.05 mg/L provided the highest effect on both germination and root growth. Expression analysis of genes encoding key enzymes in germination processs of soybean such as: Aminocyclopropane-1-carboxylic acid synthase 2 (ACS2), Lypoxygenase 3 (LOX9-03), Lypoxygenase 7 (LOX9-07), Amylase 8 (AMY8), Saccharogen amylase (AMYS), Alpha-glucan dikinase (α-GLU), Urease 2 (URE02), Urease 14 (URE14) indicated that the expression of most studied genes were increased significantly in primary roots of nano treated seeds compared to the control. The obtained results can be a scientific evident to support the application of nano products in agricultural practice